Comprehensive assessment of groundwater management in rural schools in Tandil, Argentina - Nicora, Bethania (2021)
[Introduction]:  Uncoordinated and fragmented management of water resources prevails in Latin America due to the use of sectoral approaches and the lack of information and systematization. Integrated Water Resources Management (IWRM), an approach that aims at the combined consideration of social, economic, and ecological dimensions based on intersectoral management and integrated planning, is widely recognized as appropriate to respond to the challenges of sustainable management. [Objective]: The objective was to analyze comprehensively the physical-natural and social variables that define the problem of drinking water in rural schools in Tandil county. [Methodology]: Physicochemical and microbiological analyzes were conducted to determine the potability of the resource. An index of the level of water management in schools was developed and applied, and an interview was conducted with a key Tandil School Council informant to evaluate institutional management of the resource. Finally, the variables researched were analyzed on a comprehensive basis. [Results]: Results indicated that microbiologically the water is not suitable for consumption in 73 % of the schools and that institutional management lacks conceptualization of integral management. [Conclusions]: Based on the results, it is concluded that such management directly influences the quality of water, as it is evidenced in the microbiological problems detected. The main shortcomings of the current management are identified and the need to assume institutional measures that tend to a comprehensive management of the resource is highlighted.